Money Supply Determinants in Nepal: A Macro Analysis - Tiwari, Saraswoti (Economic Literature, 2018)
This paper analyzes the major money supply determinants in Nepal in the past 10 years from FY 2004/05 - FY 20014/15. In this study monetary base is determined by two explanatory variables (i.e. NFA and NDC) and are called the 'proximate' determinants of the base money. Among the explanatory variables, the net foreign asset (NFA) is found as better determinant than net domestic assets (NDA) in Nepalese economy. For the analysis of determinants of money multiplier (MM), the three explanatory variables i.e., reserve to total deposits ratio (r), time deposits to demand deposits ratio (t) and currency to demand deposits ratio (c) have been used. The model applied in this study shows that explanatory variable of time deposits to demand deposits ratio is the best determinant of money multiplier. The reserve money (RM) is analyzed as the best determinant of money supply, net foreign assets (NFA) is the major determinant of reserve money and time deposits to demand deposits ratio is the significant determinant of money multiplier. Economic Literature, Vol. XIII August 2016, page 55-60